Multiparty Turn Taking in Situated Dialog: Study, Lessons, and Directions - Bohus, Dan; Horvitz, Eric (2011)
We report on an empirical study of a multiparty turn-taking model for physically situated spoken dialog systems. We present subjective and objective performance measures that show how the model, supported with a basic set of sensory competencies and turn-taking policies, can enable interactions with multiple participants in a collaborative task setting. The analysis brings to the fore several phenomena and frames challenges for managing multiparty turn taking in physically situated interaction.